Aggression and Hypothyroidism in Dogs, an-Overview - Atanaskova Petrov, Elena (International Journal of Zoology and Animal Biology, 2022)
One of the most often diagnosed endocrine disorder in middle-aged dogs is hypothyroidism. The clinicopathological aspects of the disease are well known and established by the scientific community. For over 20 years the relationship between aggression and hypothyroidism has been reported in the literature. Still the link remains speculative due to lack of overhaul scientific data. The aim of this study is to present data from the literature relating to the association of aggression with hypothyroidism in dogs.
Keywords: Hypothyroidism; Aggression; Dog